2019
DOI: 10.1111/bph.14826
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemokines and chemokine receptors in pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is characterized by progressive pulmonary artery remodelling leading to increased right ventricular pressure overload, which results in right heart failure and premature death. Inflammation plays a central role in the development of PAH, and the recruitment and function of immune cells are tightly regulated by chemotactic cytokines called chemokines. A number of studies have shown that the development and progression of PAH are associated with the dysregulated expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 140 publications
(283 reference statements)
1
38
1
Order By: Relevance
“…CCR5 is expressed in the macrophages, pulmonary artery endothelial cells, and pulmonary artery smooth muscle cells. Inhibition of CCR5 expression in mice model decreased perivascular macrophages recruitment and the proliferation of pulmonary-artery smooth muscle cell during hypoxia exposure (Mamazhakypov et al, 2019). However, this finding is contrary to previous studies which have suggested that CCL5 plays an important protective role in hypertension-induced renal injury.…”
Section: Hypertensioncontrasting
confidence: 83%
“…CCR5 is expressed in the macrophages, pulmonary artery endothelial cells, and pulmonary artery smooth muscle cells. Inhibition of CCR5 expression in mice model decreased perivascular macrophages recruitment and the proliferation of pulmonary-artery smooth muscle cell during hypoxia exposure (Mamazhakypov et al, 2019). However, this finding is contrary to previous studies which have suggested that CCL5 plays an important protective role in hypertension-induced renal injury.…”
Section: Hypertensioncontrasting
confidence: 83%
“…7C). As CD69 is an activation marker and CXCR4 directs cells to various tissues, including the inflamed and damaged lung (Mamazhakypov et al, 2019), these observations support a model whereby activated bystander T cells recruited to the lung lead to poor disease outcome.…”
Section: Resultsmentioning
confidence: 69%
“…S3), and compared them between the 3 patient groups for the following cell populations: Baseline, Bystander, and SARS-CoV-2-specific. Among baseline samples, CD4+ and CD8+ T cells from severe cases expressed significantly higher levels of activation markers HLADR, CD69, CD25, and PD1, as well as chemokine receptor CXCR4, which directs cells to inflamed and damaged lung tissues (Mamazhakypov et al, 2019), relative to mild cases. Among SARS-CoV-2-specific T cells, antigens significantly upregulated in severe relative to mild cases included the activation/exhaustion markers PD1 and TIGIT.…”
Section: Resultsmentioning
confidence: 99%
“…Even in the absence of overt inflammatory phenotypes, IPAH patients exhibit mild signs of systemic chronic inflammation, as evidenced by increased circulating cytokines including interleukins 71 and chemokines 72 . Importantly, a majority of these inflammatory mediators have been found to predict the survival of PAH patients 71,72 .…”
Section: Introductionmentioning
confidence: 99%